PRODUCTIVITY AND QUALITY OF TRITICUM DURUM VARIETIES IN THE CONTRAST CONDITIONS OF MOISTURE SUPPLY OF THE STEPPE OF ORENBURG PRE-URALS - T. A. Timoshenkova; I. V. Reshetova (Зерновое хозяйство России, 2018)
The article presents an analysis of productivity of the present varieties of durum spring wheat in the steppe part of Orenburg Pre-Urals during 2005-2014. The peculiarities of effect of moisture conditions on the change of productivity and technological properties of wheat have been estimated. In the dry years there was a decrease of grain mass, content of protein and gluten quality. The varieties of Samara breeding showed the largest decrease of test weight, and the varieties of Orenburg breeding showed the smallest decrease. The varieties of Samara breeding showed the smallest decrease of protein contents in grain. The varieties of Ukraine breeding showed the most negative effect of dry conditions on their properties. In the dry years in comparison with the wet years there is an increase of the total vitreousness. The varieties of Ukraine and Samara breeding showed the largest increase of it. It is necessary to use the varieties which were found less depressive to dry conditions for more efficient grain production. If the studied varieties are cultivated under limited conditions of GOST in the steppe of Orenburg Pre-Urals, the grain production of 1-3 class can be obtained.